Health Counseling and Osteoporosis Gymnastics Training for Elderly Posyandu Cadres in Kentingan Kulon, Jebres Village, Surakarta - Erika Dewi Noorratri; Rini Widarti (Urecol Journal. Part F: Community Development, 2021)
Indonesia is a country with the most population in the world, the 4th and the top ten countries have the oldest population in the world. The total number of elderly people reached 23,658,214 people in 2017. Aging is a normal process of change related to time, which begins at birth and continues throughout life. The aging process will have an impact on various aspects of life, both social, economic and health. Viewed from the health aspect, with increasing age, the elderly is more susceptible to various physical complaints, both due to natural factors and disease factors. Elderly cadres are able to understand the importance of doing physical activity, one of which is osteoporosis exercise lectures and demonstrations about gymnastics osteoporosis. The elderly cadres can understand the benefits and goals of osteoporosis exercise, can practice osteoporosis exercise independently. The elderly cadres can understand the benefits and goals of osteoporosis exercise as evidenced by the results of pretest and posttest; elderly cadres can practice osteoporosis exercise independently.